Sensitivity to scale of willingness‐to‐pay within the context of menorrhagia. (23rd February 2016) - Sanghera, Sabina; Frew, Emma; Gupta, Janesh Kumar; Kai, Joe; Roberts, Tracy Elizabeth
Abstract: Objectives: Willingness‐to‐pay (WTP) provides a broad assessment of well‐being, capturing benefits beyond health. However, the validity of the approach has been questioned and the evidence relating to the sensitivity of WTP to changes in health status is mixed. Using menorrhagia (heavy menstrual bleeding) as a case study, this exploratory study assesses the sensitivity to scale of WTP to change in health status as measured by a condition‐specific measure, MMAS, which includes both health and non‐health benefits. The relationship between EQ‐5D and change in health status is also assessed. Methods: Baseline EQ‐5D and MMAS values were collected from women taking part in a randomized controlled trial for pharmaceutical treatment of menorrhagia. Following treatment, these measures were administered along with a WTP exercise. The relationship between the measures was assessed using Spearman's correlation analysis, and the sensitivity to scale of WTP was measured by identifying differences in WTP alongside differences in MMAS and EQ5D values. Results: Our exploratory findings indicated that WTP, and not EQ‐5D, was significantly positively correlated with change in MMAS, providing some evidence for convergent validity. These findings suggest that WTP is capturing the non‐health benefits within the MMAS measure. Mean WTP also increased with percentage improvements in MMAS, suggesting sensitivity to scale. Conclusion: When compared to quality of life measured using the condition‐specific MMAS measure, the convergent validity and sensitivity to scale of WTP is indicated. The findings suggest that WTP is more sensitive to change in MMAS, than with EQ‐5D.